Albendazole suppresses cell proliferation and migration and induces apoptosis in human pancreatic cancer cells. Issue 5 (June 2020) - Chen, Haifeng; Weng, Zhen; Xu, Chunfang
Abstract : This study aims to investigate the effects of albendazole on pancreatic cancer cells and to explore the possible mechanisms involved. MTT, colony formation, wound healing and Transwell assays and immunocytochemistry analyses of proliferation antigen Ki-67 were employed to evaluate the role of albendazole in pancreatic cancer cell line proliferation and migration. Moreover, flow cytometry cell apoptosis evaluation was used for mechanism analysis. Finally, the in-vivo effects of albendazole were examined in an in-vivo nude mouse xenograft model. Compared to the control treatment, albendazole significantly decreased the growth of the pancreatic cancer cell lines SW1990 and PANC-1 in a time- and dose-dependent manner, as evidenced by decreased MTT absorbance, colony number and Ki-67 levels. Furthermore, albendazole decreased cell migration in 2- and 3-dimensional models in a dose-dependent manner. In addition, albendazole increased the apoptotic cell ratio in a dose-dependent manner. Finally, the in-vivo results confirmed that albendazole could decrease tumor growth. We demonstrated the inhibitory effects of albendazole on pancreatic cell proliferation and migration in vitro and in vivo, which indicate that albendazole might serve as a novel treatment modality for pancreatic cancer.